Association between beat-to-beat blood pressure variability and vascular elasticity in normal young adults during the cold pressor test. Issue 8 (February 2017) - Xia, Yufa; Wu, Dan; Gao, Zhifan; Liu, Xin; Chen, Qian; Ren, Lijie; Wu, Wanqing
Abstract : Abstract: The beat-to-beat blood pressure (BP) monitoring parameters, such as average beat-to-beat BP, BP variability (BPV), could have an influence on the vascular elasticity. This study hypothesized that the elevated beat-to-beat BPV could evoke the reduction of the vascular elasticity independent of BP levels. We measured the beat-to-beat BP recordings and total arterial compliance (TAC), which was used to assess the vascular elasticity, in 80 young healthy adults during the cold pressor test (CPT). The CPT included 3 phases: baseline phase, cold stimulus phase, recovery phase. Six parameters were used to estimate BPV. In bivariate correlation analysis, TAC showed a significant correlation with systolic BP (SBP) and diastolic BP (DBP) in the cold stimulus phase; and 4 indices of SBP variability (SBPV) were associated with TAC ( r  = 0.271∼0.331, P  ⩽ 0.015) in the recovery phase; similarly, 2 indices of DBP variability (DBPV) were also correlated with TAC ( r  = 0.221∼0.285, P  ⩽ 0.048) in the recovery phase. In multivariate regression analysis, DBPV ( β  = 0.229, P  = 0.001) was a determinant of TAC independent of average DBP, sex, and weight. In addition, both beat-to-beat BP and BPV values increased in the cold stimulus phase ( P  < 0.01); whereas, the TAC decreased in the cold stimulus phase ( P  < 0.01). In conclusion, these data suggest that the beat-to-beat DBPV shows an independent association with the vascular elasticity in young normal adults during the CPT.